RANCANG BANGUN PERILAKU BUATAN PADA NON-PLAYER CHARACTER DALAM GAME PEMADAM KEBAKARAN MENGGUNAKAN FINITE STATE MACHINE DAN GODOT SCRIPT - Wiriasto, Giri Wahyu; Fikriansyah, Muhammad; Rachman, A. Sjamsjiar (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2023)
The application of artificial behavior in the object character of a game that is played using a computer device continues to grow. The implementation of the algorithm in the game makes game object characters that can move autonomously according to changes in scenario roles making the game more attractive to human players. This autonomous computer player behavior is known as a non-player character (NPC). In this research a game has been developed in the category of role-playing game (RPG) which is called the Fire Extinguisher Game. In this game there is an NPC character